Prevalence and intensity of infection by helminths in bovines from the dairy basin of São Carlos, SP, Brazil - Oliveira, Gilson Pereira de; Matsumoto, Takashi (Pesquisa Agropecuaria Brasileira, 2014)
On a preliminary study of bovine helminths on dairy herds of São Carlos, SP, Brazil, that includes the counties of São Carlos, Ribeirão Bonito and Dourado, 74 holstein-zebu mixed breeding animals, 8 to 20-month old, were necropsied. From the gastrointestinal tract, lung and pancreas material was collected, and the prevalence of infection and average worm burden of species of helminths observed were: Haemonchus contortus 100% and 988.06 Haemonchus similis, 43.24% and 50.01; Trichostrongylus axei, 24.32% and 16.00; Cooperia punctata 100% and 3,649.45; Cooperia pectinata, 44.59% and 436.70; Bunostomum phlebotomum, 9.45% and 3.17; Oesophagostonum radiatum, 86,48% and 138.35; Trichuris discolor, 21.62% and 7.44; Agriostomum wryburgi, 2.70% and 0.22; Dictyocaulus viviparus, 13.51% and 51.62; Eurytrema coelomatium, 14.86% and 27.67.